The spoken language in a multimodal context : description, teaching, translation - Falbe, Sandra; Brumme, Jenny (Sprachwissenschaft, 2014)
Recently, research in the Humanities is showing an increasing interest in exactly how language and other semiotic resources support each other. The eighteen articles of this book focus on the interplay between spoken language and other modalities and address a spectrum of cross-modal resources and their functions. They also discuss how multimodal resources are exploited to increase communicative effectiveness and broaden accessibility to knowledge. This is illustrated with examples from discourse types including dramatic, literary and audiovisual texts, Facebook communication and chats, comics.